PENGARUH PROFITABILITAS, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Syuhadak, - (2019)
This study aims to determine the effect of Profitability proxied with Return On Assets (ROA), Capital Structure by Debt to Equity Ratio (DER), and Liquidity proxied by Loan to Deposit Ratio toward Firm Value proxied by Price to Book Value (PBV). The population in this research were 42 commercial banks listed on the Indonesia Stock Exchange period 2015 to 2017. The sample obtained in this study amounted to 30 commercial banks selected by purposive sampling method. Total observation data obtained in this study are 90 data period 2015 to 2017. The analysis technique that used in this study is panel data regression and hypothesis test used in this study is a statistical t-test with a confidence level of 5%.. Data analysis was done using Microsoft Excel 2010 and hypothesis testing in this research using Data Panel Regression Analysis with E-Views 9.0 program and significance level of 5%. The result of the research shows that (1) profitability (ROA) has a positive effect on firm value (PBV), (2) Capital Structure (DER) has positive effect on firm value (PBV), (3) Liquidity (LDR) has not effect on firm value (PBV).